Standar Pendidikan Anak Usia Dini Raudhatul Athfal (RA) Nurul Haq Kalisabuk Cilacap (Studi Standar Isi Ruang Lingkup Materi Pendidikan Anak Usia Dini) - Wulandari Retnaningrum (Muaddib: Jurnal Pendidikan Agama Islam, 2025)
Early childhood, known as the "golden age," is a crucial period during which a child's brain develops at an extraordinary rate and plays a crucial role in development. Quality education for early childhood is crucial and key to establishing the foundations for development. High-quality early childhood education (PAUD) requires content standards in learning activities as a foundation to significantly improve children's growth and development, thus preparing them for further education. The content standards for Early Childhood Education, as stipulated in the Minister of Primary and Secondary Education Regulation No. 12 of 2025, are designed to define the scope of material that aligns with the expected developmental milestones at specific ages, as defined by the Child Development Achievement Level Standards (STPPA). Learning activities at Raudhatul Athfal Nurul Haq, Kalisabuk, Cilacap, align with the content standards for Early Childhood Education, stipulated in the Minister of Primary and Secondary Education Regulation No. 12 of 2025. This is evident when the author collected data at Raudhatul Athfal Nurul Haq, Kalisabuk, Cilacap. Early childhood developmental outcomes covering religious and moral values, Pancasila values, physical motor skills, cognitive, language, and social emotional values ​​have been achieved in accordance with the child's age level. There is an advantage in learning outcomes in the aspect of religious and moral development for the graduation of students at Raudhatul Athfal Nurul Haq, Kalisabuk, Cilacap. Thus, Raudhatul Athfal Nurul Haq Kalisabuk Cilacap has met the content standards in terms of material scope, and learning outcomes that are in accordance with graduate competencies.